Quantum interaction 5th international symposium, QI 2011, Aberdeen, UK, June 26-29, 2011 : revised selected papers - Song, Dawei (Lecture notes in computer science, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 5th International Symposium on Quantum Interaction, QI 2011, held in Aberdeen, UK, in June 2011. The 26 revised full papers and 6 revised poster papers, presented together with 1 tutorial and 1 invited talk were carefully reviewed and selected from numerous submissions during two rounds of reviewing and improvement. The papers show the cross-disciplinary nature of quantum interaction covering topics such as computation, cognition, mechanics, social interaction, semantic space and information representation and retrieval.